1976
DOI: 10.1161/01.str.7.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Long-term EKG monitoring in patients with cerebrovascular insufficiency.

Abstract: SUMMARY Cardiac dysrhythmia may be responsible for signs of cerebrovascular insufficiency in some patients. Ten patients with cerebrovascular insufficiency were monitored for up to 24 hours with the Holter EKG monitor. Eight of the patients had transient ischemic attacks and two had mild deficits from a completed stroke. Eight of the ten patients had associated abnormal cerebral angiography, the most frequent finding being carotid stenosis. Holter EKG monitoring in these ten patients showed no abnormalities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…The remaining 2 patients who were described as having transient ischemic attacks had symptoms equally well explained on the basis of global ischemia. In the study of McHenry et al 7 6 of 10 patients with cerebral ischemic symptoms had cardiac arrhythmias and 8 had angiographic proof of significant cerebrovascular disease. The arrhythmias ranged from ventricular ectopics to intraventricular conduction defects and it was suggested that these cardiac abnormalities could account for the neurological event.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The remaining 2 patients who were described as having transient ischemic attacks had symptoms equally well explained on the basis of global ischemia. In the study of McHenry et al 7 6 of 10 patients with cerebral ischemic symptoms had cardiac arrhythmias and 8 had angiographic proof of significant cerebrovascular disease. The arrhythmias ranged from ventricular ectopics to intraventricular conduction defects and it was suggested that these cardiac abnormalities could account for the neurological event.…”
Section: Discussionmentioning
confidence: 98%
“…At the present time there is available a non-invasive method to measure regional cerebral blood flow. This was originally described by Mallett and Veall Corbett and Eidelman, 6 and by Meyer et al 7 Normal values as well as test-retest results were described by Blauenstein and his associates. 8 The background of the xenon-inhalation method has been discussed by Merory et al 9 and Meyer et al 7 ' 10 The purpose of this paper is to report the results of regional cerebral blood flow measurements by the xenon inhalation method in normal individuals and to test the reproducibility of the method by serial measurements.…”
mentioning
confidence: 86%
“…Two studies, however, have shown that vasodilator response was reduced or impaired in only 25% of patients with cerebral circulatory disturbances." 7 ' m Mathew et al 101 noted, in 6 patients with recent hemispheric infarction, that CBF was increased in all regions after CO 2 inhalation. It is generally agreed that the steal response occurs only during the acute stages of severe and extensive cerebral infarction, and then only rarely.…”
Section: Blood Gas Therapymentioning
confidence: 99%
“…It has been suggested that an osmolar gradient of about 30 mOsm is desirable for achieving an adequate dehydrating action; 79 ' u * yet the improvement in hemispheric 1 " or regional 125 blood flow is noted at 14-20 mOsm. Dehydrating agents have also been criticized as having only short-lived efficacy, 7 ' 1 "' but Newkirk et al 1 " were able to demonstrate control of intracranial pressure continuously for 3 weeks using oral glycerol.…”
Section: Dehydrating (Antiedema) Agentsmentioning
confidence: 99%
“…6 ' 7 Several authors have alluded to the role of a diminished cardiac output in various dysrhythmias as an etiologic agent in transient focal cerebral ischemia and the need for continuous ECG monitoring in these patients. 8 ' 9 Others have stressed the rarity of transient focal cerebral events in dysrhythmias associated with a significant reduction in cardiac output. 10 A recent experience with a patient who had significant cardiac dysrhythmias and transient focal cerebral ischemic symptoms which did not abate after cardiac pacing prompted a review of Holter monitoring results in patients with such transient focal cerebral symptoms.…”
mentioning
confidence: 99%